Editorial for Vol.32, No.3 - Alan Jović (Journal of Computing and Information Technology)
The September 2024 (Vol. 32, No. 3)issue of CIT. Journal of Computing and Information Technology brings four papers from the areas of power load forecasting, fault diagnosis, recommender systems, and biomedical data mining.